Adrenomedullin as a Protein with Multifunctional Behavior and Effects in Various Organs and Tissues - Ozcelik, Fatih; Hanim Pence, Halime; Yalcin Ozturkeri, Hilal; Sertoğlu, Erdim (International Journal of Negative Results, 2019)
In literature, it has been reported that adrenomedullin, which is generally thought to have vasodilator, natriuretic and diuretic effects, is synthesized in almost all body, especially CNS, vascular muscles and endothelium, heart, liver, lung, kidney, gastric mocosa, intestinal endothelium and various blood cells. It has been found that the possible effects of adrenomedullin can be demonstrated directly or indirectly by means of active mediators, neuropeptides, enzymes and hormones. It is also suggested that it regulates the endocrine system by affecting the hypothalamic-pituitary axis. It increases in heart failure, acute coronary syndromes, hypertensive conditions, cerebrovascular accessory, chronic renal failure and periodontitis and decreases in peptic ulcer and intestinal diseases. However, it is still not clear whether increase/decrease in adrenomedullin level is a cause of a disease or is a result of damage due to an illness. This peptide, which could be thought to multifunctional, should be considered as a molecule with genetic coding that may have different effects on different tissues and conditions. For all these reasons, we aimed to review the multifonctional behavior of adrenemedullin in the light of the current literature to pioneer new hypotheses and discuss possible mechanisms.
Keywords: Adrenomedullin; Multifonctional behavior of ADM; Effects and synthesis of ADM.